Perkembangan Masjid Kemayoran Surabaya Ditinjau dari Teori Peran Levinson - Syafitri, Ainiya (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
This study aims to reveal the development of a religious, social, and educational foundation, namely the Ta'mirul Mosque Kemayoran Surabaya Foundation. The progress of a foundation is one of the important indicators for the progress of society, even a country, at the macro level. Indonesia has hundreds of thousands of foundations that have grown up, but unfortunately many have ended up in suspended animation due to mismanagement. The Ta'mirul Masjid Kemayoran Surabaya Foundation is interesting to study because it can grow big, progressed, and exist until now, which of course has a long and not easy historical experience. This study uses historical research methods and a sociological approach, then analyzed using Levinson's role theory. The results of this study revealed that the Ta'mirul Mosque Kemayoran Surabaya Foundation was founded. This foundation was founded on March 3, 1976, by several figures, namely Ir. Facthurrahman Murtadlo, Mohammad Sjahid Alfata, Mohammad Sururi Murtadlo, Drs. Miftach. Traced from the chronology of the development of the foundation, it has made quite rapid progress as evidenced by complete infrastructure, the density of mosque activities, the rise of social philanthropy, and there are advanced educational institutions ranging from kindergarten to high school. This development cannot be separated from the many factors supporting progress along with the inhibiting factors. The solutions to the elements that hinder progress include: building commitment between the management, determining priorities, and coordinating with related parties.